Modelling of fast transients in transformer windings = Modeliranje brzih prijelaznih pojava u namotima transformatora : specialist thesis = specijalistički rad - Jurman, Andrej (A. Jurman ; Fakultet elektrotehnike i računarstva, 2012)
ABSTRACT The aim of the thesis is the description of calculation of voltages appearing during lightning impulse test, i.e. so called transient calculation. The general lumped parameters model is described together with possible way of calculation of its electrical parameters based on finite elements method. The simplified model is introduced and its solution with software for electrical circuit calculation is presented. The calculation results are compared to the recurrent surge oscillograph measurements on real power transformer. At the end the possibility of introduction of non-linear varistors in the calculation model is shown.